2016
DOI: 10.3390/su8010065
|View full text |Cite
|
Sign up to set email alerts
|

Walkability, Land Use and Physical Activity

Abstract: Physical activity (PA) promotes healthy life and contributes to sustainable development. In this paper, we rely on the Utah Household Travel Survey data and analyze the determinants of PA in terms of neighborhood land use, accessibility to transportation, and socio-demographic status in Salt Lake County, Utah, United States using four-component walkability indices at various geographic scales. We find that PA is associated with neighborhood land use and social demographic status, including the compact design o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 77 publications
(69 reference statements)
2
35
1
1
Order By: Relevance
“…Despite some studies [19] finding land use mix to be insignificant to PA, a relatively strong relationship between land use mix entropy and the PA level was found for the older people living in the terraced housing in Taman Perling. The high land use mix value indicated that the respondents were C1, which was unlikely to happen as older adults would usually show high levels of PA in high mixed land use neighbourhoods [20].…”
Section: Model 1 (Perling Terrace)contrasting
confidence: 60%
See 1 more Smart Citation
“…Despite some studies [19] finding land use mix to be insignificant to PA, a relatively strong relationship between land use mix entropy and the PA level was found for the older people living in the terraced housing in Taman Perling. The high land use mix value indicated that the respondents were C1, which was unlikely to happen as older adults would usually show high levels of PA in high mixed land use neighbourhoods [20].…”
Section: Model 1 (Perling Terrace)contrasting
confidence: 60%
“…Other studies have found that PNEO measures such as land use mix entropy [19][20][21], population density [19,21,22], traffic intersection density [13,[23][24][25][26] and proximity to recreation areas [26][27][28] influence the PA levels of older adults. While these types of PNEO measures are reliable in representing the objective physical characteristics of the neighbourhood environment that can strongly influence the PA level in older adults, in some cases, local considerations are also needed.…”
Section: Formulation Of Conceptual Modelmentioning
confidence: 96%
“…In contrast, bonding capital has been described as the "dark side" of social capital and has the potential to be oppressive, exacerbating segregation, and producing illiberal effects [2]. Given that many Americans spend more time in churches than any other type of voluntary organizations [18], church involvement appears to have great potential to foster "bridging social capital" rather than "bonding social capital" [19].…”
Section: Social Capital Racial Diversity and Income Inequalitymentioning
confidence: 99%
“…Land use is often operationalised using density, diversity and design measures. Areas with high densities (population, residential, commercial) usually generate more people walking, by decreasing the appeal of driving through congested areas where parking is often scarce [25,45]. Densities are usually analysed by developing ratios and indexes.…”
Section: Literature Reviewmentioning
confidence: 99%